Pengelolaan Dana Bantuan Operasional Sekolah Di SMK Batik 1 Surakarta - Ahmad Turmudi; Yuwita Ariessa Pravasanti; Darmanto Darmanto (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2022)
The study was to determine the effective, efficient, and transparent processing of BOS management at SMK Batik 1 Surakarta. This research is a qualitative descriptive study. In this qualitative research, interviews and observations as well as document reviews are the main data collection methods. The data was analyzed in 3 steps, namely: data collection, data reduction, and data display. The result of BOS report at SMK Batik 1 Surakarta was credible. It can be credible because it was showing effectiveness and efficiency. The evidence was the budget plan is by the outcome of the expenses budget. SMK Batik 1 Surakarta also strives to expose the results of the BOS management to all parties involved.